The role of athletic mental energy in the occurrence of flow state in male football (soccer) players - Yarayan, Y. E.; Batrakoulis, A.; Güngör, N. B.; Kurtipek, S.; Keskin, K.; Çelik, O. B.; Gülsen, D. B. A.; Grivas, G. V.; Al-Mhanna, S. B.; Alkhamees, N. H.; Sheeha, B. B.; Alghannam, A. F. (BMC Sports Science, Medicine and Rehabilitation, 2025)
Background This study examines the determinant role of athletic mental energy on the flow state in professional football (soccer) players. This research fills an important gap in the sports psychology literature by focusing on the interaction between mental energy and flow, a critical component of optimal performance.